2011
DOI: 10.1017/s1041610211000123
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, chronic medical illness, and health care utilization: findings from the Korean Longitudinal Study of Ageing (KLoSA)

Abstract: Background: This population-based study examined the relative and combined relationships of chronic medical illness (CMI) and depressive symptoms with health care utilization among older adults in South Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…In the KLoWF, the CES-D 10 has values ranging from 0 to 30, with a score of 30 indicating the most severe depressive symptoms. This Korean version of CES-D 10 has been reported as valid in previous studies [32,33].…”
Section: Depressive Symptomsmentioning
confidence: 85%
“…In the KLoWF, the CES-D 10 has values ranging from 0 to 30, with a score of 30 indicating the most severe depressive symptoms. This Korean version of CES-D 10 has been reported as valid in previous studies [32,33].…”
Section: Depressive Symptomsmentioning
confidence: 85%
“…18 Inequality in inpatient or outpatient service utilization has remained even after adjusting for health status among older adults. 19 A literature review showed that income, wealth, education, previous or current employment status, housing, and region were predictors of health expenditure among older people. 20 Under the relatively weak Korean social pension system, older people with low incomes faced considerable financial burden due to health expenditures, resulting in lower health care service use.…”
Section: Aging and Healthmentioning
confidence: 99%
“…People with mental illness, such as psychotic illness, have significantly poorer physical health compared to the general population (Kim et al . ; Laursen et al . ; Scott et al .…”
Section: Introductionmentioning
confidence: 99%